Deep-sea amphipod fauna of the Sea of Okhotsk. (November 2019) - Frutos, Inmaculada; Jażdżewska, Anna Maria
Highlights: The family diversity of amphipods rises up in the Sea of Okhotsk. Deep-sea amphipod distribution is characterised by environmental variables. Depletion of oxygen content decreases the occurrence of deep-sea amphipods. New taxa to science are identified in the Sea of Okhotsk. Abstract: During joint Russian-German SokhoBio expedition held in 2015, the deepest area of the Sea of Okhotsk (Kuril Basin), the Bussol Strait and the western abyssal slope of the Kuril-Kamchatka Trench were investigated using camera epibenthic sledge. In total, 19 stations ranged between 1696 and 4798 m depth were sampled. The amphipods constituted 10% of all macroinvertebrates and one fourth of all Peracarida. The identification of families resulted in 32 taxa of which two (Liljeborgiidae and Valettiopsidae) were recorded for the first time from the Sea of Okhotsk. The most abundant group was Corophiida (17.4%), followed by the Oedicerotidae (15.8%), the Phoxocephalidae (12.3%), and the Eusiridae (11.7%). A multivariate analysis carried on the amphipod family abundance data (three stations excluded), discriminated four different assemblages in the studied area: a Bussol Strait assemblage (group A, two stations, 2327–2333 m) dominated by Corophiida group; a Kuril Basin assemblage (group B, 11 stations, 3210–3366 m) characterized by Oedicerotidae and Phoxocephalidae; and two assemblages in the Kuril-Kamchatka Trench area: a single station (group C, 4681 m) dominated by Phoxocephalidae and two grouped stations (group D, 3371–4798 m) characterized by Lysianassoidea. The effect of environmental variables on amphipod taxocenosis was also discussed.